Association between sporadic Parkinson disease and interleukin-1 beta-511 gene polymorphisms in the Turkish population - ARMAN, AHMET (JOHN LIBBEY EUROTEXT LTD, 2010)
The pathogenesis of Parkinson Disease (PD) remains poorly understood; however, inflammation is thought to play an important role in disease progression. Recent reports suggest that IL-1, a major proinflammatory cytokine, might play a role in PD progression. The purpose of this study was to determine the relationship between IL-1 gene family polymorphisms [IL-1 alpha (-889), IL-1Ra (VNTR) and IL-1 beta (-511, +3953)] and PD in the Turkish population. In this study, we examined the genotypes of IL-1 gene family polymorphisms in 365 individuals, of which 199 were healthy control subjects and 166 were PD patients. No significant differences were found in the genotype distribution or in the allele frequencies of IL-1 alpha (-889), IL-1Ra (VNTR) and IL-1 beta (+3953) between PD cases and control subjects. However, distribution of the IL-1 beta -511 2/2 (T/T) genotype was found to be significantly lower in PD patients than in healthy controls (p = 0.018, x(2): 8.242, OR: 2.211, 95% CI: 1.261-3.877). In addition, the IL-1 beta -511 allele 1 (C) frequency was significantly elevated in PD patients versus controls (p = 0.048, x(2): 3.87, OR: 1.178, 95% CI: 0.999-1.388). These results suggest that IL-1 alpha (-889), IL-1Ra and IL-1 beta (+3953) gene polymorphisms have no association with PD, while allele 1 (C) of IL-1 beta (-511) is associated with PD and may provide a susceptibility factor for this disease in the Turkish population. Furthermore, the 2/2 (T/T) genotype of IL-1 beta (-511) may protect individuals from PD.
Keywords: interleukin-1; cytokine; polymorphism; Parkinson disease; RECEPTOR ANTAGONIST GENE; CEREBROSPINAL-FLUID; ONSET; IL-1; INTRON-2; INFLAMMATION; RISK; RATS